PENGARUH LAPORAN PENGGUNAAN DANA ZAKAT KONSUMTIF, ZAKAT PRODUKTIF, INFAK TERIKAT DAN INFAK TIDAK TERIKAT TERHADAP PENINGKATAN DANA ZAKAT, INFAK, SEDEKAH - Hani Muflihah; Soleh Rosyad (Universitas La Tansa Mashiro, 2019)
Zakat, infak and sedekah is an important instrument for building prosperity. Consumptive zakat and productive zakat is an important instrument of zakat., because it’s base distribution in Amil Zakat Institution. It’s so distribution with alm infak an alm infak not tied should do be good finances report should responsibility. Finance report at Zakat Institution is base to prospective donors see the development and distribution and they have contributed ZIS.This reseach method using kuantitatif. For find out are there positive influence at consuntive zakat, productive zakat, alm infak, and alm infak not tied to the increase in agency ZIS Amil Zakat enlisted a member in Zakat Forum (FOZ)Indonesia.To analyze the impact report on the use of consumptive zakat, productive zakat, alm infak, and alm infak not tied found to increase ZIS regression analysis multiple with Ordinary Least Squared (OLS) method. Reseach object is Amil Zakat Constitution (LAZ) in alliance Forum Zakat (FOZ) Indonesia, they are 17 institution. Research using data secondary it is get of 17 Amil Zakat Institution of finece report 2014-2015. From the result of reseach show the report on the use of consumptive zakat, productive zakat, and alm infak found have a influence on the increase in ZIS. And while report on the use of alm infak not tied found have not a positive influence on the increase in ZIS. Report on the use consumptive zakat, productive zakat, alm infak and alm infak not tied when tested at the same time has an influence on the increase ZIS. Effect level is the strongest. Effect level of 94.4 % but 5.6 % is influence other factor beyond the reseach.